The Distribution Pattern of Ocular Residual Astigmatism in Chinese Myopic Patients - Tang, Changting; Du, Zijing; Wu, Guanrong; Tan, Xuanyun; Zang, Siwen; Yu, Honghua; Hu, Yijun (Frontiers in Medicine, 2022)
Purpose: We aimed to investigate the distribution of ocular residual astigmatism (ORA) and its associations with age, gender, manifest refraction and other ocular indicators in Chinese myopic patients. Design: This is a multi-center retrospective cross-sectional study. Method: The study included 7893 myopic patients aged 18-40 years from five ophthalmic centers. Anterior segment biometrics of the eyes were collected from the Pentacam. ORA was calculated using Alpine’s vector analysis. Compensation factor (CF) was used to evaluate the relation between ORA and corneal astigmatism in J0 and J45 vectors. ORA in different age, gender and refraction groups was compared. Spearman correlation was adopted to reveal multiple ocular indicators associated with ORA, which were integrated into a multiple linear regression model to predict ORA. Results: Distribution of ORA was slightly positively skewed (Skewness= 2.111, Kurtosis = 19.660, KS P< 0.0001). Mean ORA was 0.74±0.39 D (95% normal range: 0.14D~1.54D). Among all subjects, 22.4% of the eyes had an ORA magnitude of 1.0 D or more. Under- or full-compensation of anterior corneal astigmatism (ACA) by ORA prevailed in both J0 (76.99%) and J45 (58.48%) vectors. Females had higher ORA power than males (0.77±0.36 D vs 0.73±0.41 D, P< 0.0001). Participants with less negative spherical equivalent (SE) or higher manifest astigmatism (MA) also had higher ORA (all P < 0.0001). ORA was significantly correlated with ACA (r = 0.405) and posterior corneal astigmatism (PCA, r = 0.356). Multiple linear regression analysis showed strong predictability of the ORA magnitude using SE, MA, ACA and mean anterior corneal curvature (R2:0.309, MAE: 0.215, RMSE: 0.327). Conclusion: ORA is present in Chinese myopic adults, and affected by multiple ocular factors. Our findings may provide valuable information about ORA distribution in candidates of refractive surgery, helping optimize the outcome of astigmatism correction.